Dopaminergic microtransplants into the substantia nigra of neonatal rats with bilateral 6-OHDA lesions. I. Evidence for anatomical reconstruction of the nigrostriatal pathway - Nikkah, G (J Neurosci, 1995)
Reconstruction of the nigrostriatal pathway by long axon growth derived from dopamine-rich ventral mesencephalic (VM) transplants grafted into the substantia nigra may enhance their functional integration as compared to VM grafts implanted ectopically into the striatum. Here we report on a novel approach by which fetal VM grafts are implanted unilaterally into the substantia nigra (SN) of 6-hydroxydopamine (6- OHDA)-lesioned neonatal pups at postnatal day 3 (P3) using a microtransplantation technique. The results demonstrate that homotopically placed dopaminergic neurons survive and integrate well into the previously 6-OHDA-lesioned neonatal SN region. Moreover, the tyrosine hydroxylase (TH)-positive neurons extended axons rostrally along the white matter tract of the internal capsule closely following the course of the original nigrostriatal pathway. The graft reestablished a TH-positive axon terminal network in the ipsilateral caudate-putamen, with the highest density in the medial and central parts. Retrograde labeling with Fluoro-Gold from the host striatum demonstrated that most of the transplant neurons giving rise to the graft-derived fiber outgrowth were TH-positive, but revealed also a small proportion of projecting neurons which were TH-negative. Amphetamine-induced striatal Fos expression was normalized in the caudate-putamen ipsilateral to the intranigral VM grafts, showing hyperexpression in some areas of the striatum, and the apomorphine- induced Fos expression seen in the 6-OHDA-lesioned animals was completely reversed on the grafted side. These findings indicate that the graft-derived dopaminergic reinnervation of the striatum is functional. The microtransplantation strategy may provide new avenues for the exploration of morphological and functional integration of fetal dopamine neurons in the nigrostriatal system and give new insights into the mechanisms controlling long-distance axon growth in the brain.